2022
DOI: 10.3389/fenvs.2022.937688
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Fertility and Bacterial Community Composition to Vegetation Species in a Coal Mining Subsidence Area: A Survey After 20-Year Reclamation

Abstract: Revegetation is an important restoration approach after reclamation in coal mining subsidence area. However, few studies have paid attention to the impacts of different vegetation species on soil fertility and bacterial community composition in the reclamation area filled with fly ash for a long time. In this study, soil fertility and bacterial community composition were investigated in a non-subsidence area (FCK) and a coal mining subsidence reclamation area restored vegetation with woody plants (pagoda trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Several studies examined the variations in soil properties during different reclamation periods and generally observed that soil organic matter and nitrogen content decreased significantly after the reclamation of saline soils [8]. For black soils in Northeast China, it was observed that the initial 20 years of reclamation had much higher rates of decreasing soil nitrogen and organic matter content, after which the soil nitrogen and organic matter content decreased stably [9]. To counteract the carbon and nutrient decline, enhanced fertilizer applications and strengthened nutrient management practices are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examined the variations in soil properties during different reclamation periods and generally observed that soil organic matter and nitrogen content decreased significantly after the reclamation of saline soils [8]. For black soils in Northeast China, it was observed that the initial 20 years of reclamation had much higher rates of decreasing soil nitrogen and organic matter content, after which the soil nitrogen and organic matter content decreased stably [9]. To counteract the carbon and nutrient decline, enhanced fertilizer applications and strengthened nutrient management practices are needed.…”
Section: Introductionmentioning
confidence: 99%